Manajemen Nyeri dengan Guided Imagery pada Pasien Pasca Operasi Total Joint Arthroplasty - Ahmidati, Afiif; Irawaty, Dewi; Yona, Sri; Arista, Liya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the effectiveness of guided imagery in patients after total joint arthroplasty surgery. The method used is a systematic review using literature searches from 9 databases: PubMed, Scopus, Sage, ScienceDirect, Taylor & Francis, Wiley, SpringerLink, Cochrane, and ProQuest. Fifteen thousand seven hundred forty-eight articles were obtained from the initial search using keywords related to